Optimized approach for the identification of highly efficient correctors of nonsense mutations in human diseases. - Hana Benhabiles (PLoS ONE, 2017)
About 10% of patients with a genetic disease carry a nonsense mutation causing their pathology. A strategy for correcting nonsense mutations is premature termination codon (PTC) readthrough, i.e. incorporation of an amino acid at the PTC position during translation. PTC-readthrough-activating molecules appear as promising therapeutic tools for these patients. Unfortunately, the molecules shown to induce PTC readthrough show low efficacy, probably because the mRNAs carrying a nonsense mutation are scarce, as they are also substrates of the quality control mechanism called nonsense-mediated mRNA decay (NMD). The screening systems previously developed to identify readthrough-promoting molecules used cDNA constructs encoding mRNAs immune to NMD. As the molecules identified were not selected for the ability to correct nonsense mutations on NMD-prone PTC-mRNAs, they could be unsuitable for the context of nonsense-mutation-linked human pathologies. Here, a screening system based on an NMD-prone mRNA is described. It should be suitable for identifying molecules capable of efficiently rescuing the expression of human genes harboring a nonsense mutation. This system should favor the discovery of candidate drugs for treating genetic diseases caused by nonsense mutations. One hit selected with this screening system is presented and validated on cells from three cystic fibrosis patients.